ATLAS DAS MULTIPLICIDADES DO RIO DE JANEIRO: TERRITORIALIDADES EM IMAGENS GEOLOCALIZADAS - Souza, Tasso Gasparini de (2020)
This research analyzed a dataset of geolocalized images from the city of Rio de Janeiro (Brazil) published on the online social network Twitter, from September 19 to September 27, 2017. In the first chapter, we review some theories about space and territo